Experimental paracoccidioidomycosis in hamster: transmission electron microscopy of inoculation site lesion - Coelho, K. I. R.; Takeo, K.; Yamaguchi, M.; Sano, A.; Kurita, N.; Yoshida, S.; Nishimura, K.; Miyaji, M. (Revista do Instituto de Medicina Tropical de São Paulo, 1994)
Interaction between Paracoccidioides brasiliensis (Pb) and inflammatory cells in hamster testis was studied sequentially by transmission electron microscopy. In early lesions (six hours after inoculation), polymorphonuclear neutrophils (PMNs) were the major and mononuclear cells and eosinophils were the minor constituents of the inflammatory cells. PMNs were later replaced by mononuclear cells. Viable Pb cells were phagocytosed or surrounded by inflammatory cells. Preserved Pb cells usually had broad host-parasite interphases, whereas dying ones had narrow interphases. The outer layer of the fungus wall was sometimes broken by PMN in some focal points, broken pieces being peeled off and phagocytosed. Small Pb cells were uninuclear, and were often related to broad interphase. Large Pb cells were multinucleated with irregularly shaped wall, and sometimes had lomasome and/or myelin like structures. Different interaction patterns of Pb with inflammatory cells may be due to functionally different host cell flow to the inoculation site or due to the age of Pb cells or both.